Pharmaceutical care education in Kuwait: pharmacy students' perspectives - Katoue MG; Awad AI; Schwinghammer TL; Kombian SB (Centro de Investigaciones y Publicaciones Farmaceuticas, 2014)
Background: Pharmaceutical care is defined as the responsible provision of medication therapy to achieve definite outcomes that improve patients' quality of life. Pharmacy education should equip students with the knowledge, skills, and attitudes they need to practise pharmaceutical care competently. Objective: To investigate pharmacy students' attitudes towards pharmaceutical care, perceptions of their preparedness to perform pharmaceutical care competencies, opinions about the importance of the various pharmaceutical care activities, and the barriers to its implementation in Kuwait. Methods: A descriptive, cross-sectional survey of pharmacy students (n=126) was conducted at Faculty of Pharmacy, Kuwait University. Data were collected via a pre-tested self-administered questionnaire. Descriptive statistics including percentages, medians and means Likert scale rating (SD) were calculated and compared using SPSS, version 19. Statistical significance was accepted at a p value of 0.05 or lower. Results: The response rate was 99.2%. Pharmacy students expressed overall positive attitudes towards pharmaceutical care. They felt prepared to implement the various aspects of pharmaceutical care, with the least preparedness in the administrative/management aspects. Perceived pharmaceutical care competencies grew as students progressed through the curriculum. The students also appreciated the importance of the various pharmaceutical care competencies. They agreed/strongly agreed that the major barriers to the integration of pharmaceutical care into practice were lack of private counseling areas or inappropriate pharmacy layout (95.2%), lack of pharmacist time (83.3%), organizational obstacles (82.6%), and pharmacists' physical separation from patient care areas (82.6%). Conclusion: Pharmacy students' attitudes and perceived preparedness can serve as needs assessment tools to guide curricular change and improvement. Student pharmacists at Kuwait University understand and advocate implementation of pharmaceutical care while also recognizing the barriers to its widespread adoption. The education and training provided at Kuwait University Faculty of Pharmacy is designed to develop students to be the change agents who can advance pharmacist-provided direct patient care.